2009
DOI: 10.1038/oby.2009.110
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Fat Shows Higher Thyroid Hormone Receptor‐α1 Gene Expression Than Omental Fat

Abstract: The aims of this work were to evaluate thyroid hormone receptor‐α (TRα), TRα1, and TRα2 mRNA gene expression and TRα1:TRα2 ratio, identified as candidate factors for explaining regional differences between human adipose tissue depots. TRα, TRα1, and TRα2 mRNA levels, and the gene expressions of arginine–serine‐rich, splicing factor 2 (SF2), heterogeneous nuclear ribonucleoprotein H1 (hnRNP H1), heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1), and Spot 14 (S14) were evaluated in 76 paired adipose tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 43 publications
4
31
2
1
Order By: Relevance
“…GWAT is considered to be the "pure WAT," whereas IWAT is a "convertible WAT" that may convert to BAT (31). Compared with visceral fat, subcutaneous fat cells express more thyroid hormone receptors (32) and mitochondrial Ucp1 (33,34), have more efficient insulin signaling and Glut4 (35), and are more responsive to Ppar␥ thiazolidinedione ligand (36,37). When subcutaneous fat was transplanted into the visceral cavity of mice, it reduced body weight and fat mass and enhanced insulin and glucose sensitivities (38), suggesting an intrinsic difference between the two fat pads.…”
Section: Discussionmentioning
confidence: 99%
“…GWAT is considered to be the "pure WAT," whereas IWAT is a "convertible WAT" that may convert to BAT (31). Compared with visceral fat, subcutaneous fat cells express more thyroid hormone receptors (32) and mitochondrial Ucp1 (33,34), have more efficient insulin signaling and Glut4 (35), and are more responsive to Ppar␥ thiazolidinedione ligand (36,37). When subcutaneous fat was transplanted into the visceral cavity of mice, it reduced body weight and fat mass and enhanced insulin and glucose sensitivities (38), suggesting an intrinsic difference between the two fat pads.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone exerts pleiotropic effects through modulation of gene expression by specific nuclear receptors (TR). TRa plays a central role in mediating the action of thyroid hormone and has been implicated as a major factor in the regulation of the development and function of adipose tissue (Liu et al, 2003;Jiang et al, 2004;Ortega et al, 2009;Mishra et al, 2010). Using the IMpRH panel, we first mapped the TRa gene to porcine chromosome 12.…”
Section: Discussionmentioning
confidence: 99%
“…Mammals have two principal TR isoforms (TRa and TRβ); each of them gives rise to multiple isoforms via alternate splicing or alternate start codon usage (Munoz and Bernal, 1997). Recently studies have shown that TRα isoform is predominantly expressed in adipocytes and plays a pivotal role in mediating the action of thyroid hormone in adipocytes (Ying et al, 2007;Pelletier et al, 2008;Ortega et al, 2009). Although TRa has been implicated as a major factor in the regulation of fat deposition, little is known about the age-related changes of TRa gene expression in porcine adipose tissue; there is also a lack of information on breed differences.…”
Section: Introductionmentioning
confidence: 99%
“…O efeito positivo da T3 na diferenciação osteogê-nica tem sido pesquisado nas CTM-MO de ratas jovens e saudáveis (18). Em CTM do tecido adiposo, tanto subcutâneo quanto visceral, foi comprovada a presença de receptores para os hormônios tireoidianos (19). Mas o que se sabe é que a tiroxina (T4) aumenta a síntese de IGF em culturas de CTM-TA de suínos, favorecendo a adipogênese (20).…”
Section: Introductionunclassified